PENGARUH EFIKASI DIRI, STRES KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PT GRAMEDIA ASRI MEDIA EMERALD BINTARO - Rachel Alfa Chatrina, (2022)
This research aims to determine the influence of self-efficacy, work stress and physical work environment on employee performance of PT Gramedia Asri Media Emerald Bintaro using quantitative method. This research used saturation sampling with 30 subjects and collecting data using online questionnaire. SmartPLS 3.0 application was used to analysed data and the result showed that (1) self-efficacy efficacy has significant influence on employee performance based on the path coefficients result 0.419 (2) work stress has significant influence on employee performance based on the path coefficients result 0.228 and (3) physical work environment has significant influence on employee performance based on the path coefficients result 0.358.